Čhāk pratyā khō̜ng sētthakit phō̜phīang sū kānpatibat (Samnakngān Khana Kammakān Phatthanākān Sētthakit læ Sangkhom hǣng Chāt, 2008)
On application of self-sufficiency economy philosophy in developing economic conditions in all sectors of Thailand.